Chemical composition, antioxidant and antimicrobial activity of phenolic compounds extracted from wine industry by-products. (October 2018) - Silva, Vanessa; Igrejas, Gilberto; Falco, Virgílio; Santos, Teresa P.; Torres, Carmen; Oliveira, Ana M.P.; Pereira, José Eduardo; Amaral, Joana S.; Poeta, Patrícia
Abstract: Winery by-products are a rich source of polyphenols, which have proven to have several beneficial biological properties, such as, antioxidant and antimicrobial activities. Therefore, this study aimed the extraction of polyphenols from winery by-products of two Portuguese red grape varieties, Touriga Nacional and Preto Martinho, and evaluate their phenolic profile, antioxidant properties and antimicrobial activity against antibiotic resistant bacteria. The polyphenols were extracted from the grapes' skins, seeds and stems. Extracts were analysed for total phenolic, anthocyanin and tannin contents, and the polyphenol profile was determined by High Performance Liquid Chromatography. The antioxidant activity of the extracts was determined by ABTS + and DPPH methods. Antimicrobial susceptibility assay was performed using Kirby-Bauer disc diffusion method. Preto Martinho variety presented a higher polyphenolic content than Touriga Nacional. Malvidin 3- O -glucoside was the most abundant compound found in the skins extracts in both varieties. The main phenolic compound found in the seeds and stems extracts was catechin. From the several flavonols quantified, rutin was the most abundant. For both varieties, the seeds extracts showed the highest antioxidant and antimicrobial properties, followed by the stems extracts. The extracts showed antibacterial activity against all tested strains except on gram-negative bacteria Salmonella enteritidis, Escherichia coli and Pseudomonas aeruginosa. These results show that, natural products, such as polyphenols, may represent a source for the development of novel antimicrobials to combat gram-positive resistant bacteria and possibly be used as natural food preservatives. However, they were not effective against gram-negative resistant bacteria which shows that polyphenols, alone, might not substitute antibiotics. Graphical abstract: Image Highlights: Chromatographic analysis of polyphenols extracted from grape skins, seeds and stems. The Portuguese grape cultivars by-products analyzed are rich in polyphenols. Antioxidant and antibacterial potential is more pronounced in Preto Martinho variety. Polyphenols are not effective against gram-negative antibiotic resistant bacteria.